2015
DOI: 10.1039/c4ra10808f
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3,6-unsymmetrically disubstituted-1,2,4,5-tetrazines: S-induced one-pot synthesis, properties and theoretical study

Abstract: 18 unprecedented 3,6-unsymmetrically disubstituted-1,2,4,5-tetrazines were synthesized, and their spectral and electrochemical properties are studied. A systematic theoretical investigation based on DFT calculations was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…40,41 Similarly, decreasing the electron density of the tetrazine ring by substituting positions C3 and C6 with aromatic heterocycles with different pendant EWGs increases the reaction rate against dienophiles. 42,43 The electronic effect of the number of N-heteroatoms in the heterocyclic ring was also studied by Sauer et al 44 The authors showed that tetrazine reacts significantly faster than, for example, triazine (K 2 tetrazine 4 K 2 triazine 4 K 2 pyridazine 4 K 2 pyridine; Fig. 5b).…”
Section: Features For Reactivity Of Iedda Reactantsmentioning
confidence: 93%
See 1 more Smart Citation
“…40,41 Similarly, decreasing the electron density of the tetrazine ring by substituting positions C3 and C6 with aromatic heterocycles with different pendant EWGs increases the reaction rate against dienophiles. 42,43 The electronic effect of the number of N-heteroatoms in the heterocyclic ring was also studied by Sauer et al 44 The authors showed that tetrazine reacts significantly faster than, for example, triazine (K 2 tetrazine 4 K 2 triazine 4 K 2 pyridazine 4 K 2 pyridine; Fig. 5b).…”
Section: Features For Reactivity Of Iedda Reactantsmentioning
confidence: 93%
“…75,76 Sulphur is described to react first with hydrazine to give NH 2 NHSH, which serves as an active nucleophile towards nitriles, generating a reactive intermediate that eliminates H 2 S to form the dihydrotetrazine core. 43,75,77 Importantly, although these conditions have been successfully used for the synthesis of aromatic tetrazines, very low yields are reported in the case of alkyl tetrazines. Alternatively, N-acetylcysteine was successfully tested as catalyst for the synthesis of tetrazines possibly through the formation of amidrazone intermediates.…”
Section: Synthesis Of Tetrazine Derivativesmentioning
confidence: 99%
“…The Ph substituent as R 2 induces the bathochromic shift of λ ex (Entries 1–6 and 13–16, Table 3 ) in comparison to n -Bu (Entries 7–12 and 17–20, Table 3 , red color vs. blue color in Figure S65 ). In the case of the 15a – h series, which consists of the symmetrically substituted compounds, the λ em increases together with the rising electron-donating strength of R 1 (H < t -Bu < OCH 3 ), which is typical for tetrazine derivatives [ 34 , 35 ]. A partially similar relationship is observed in the unsymmetrically substituted 10a – l series.…”
Section: Resultsmentioning
confidence: 99%
“…The iEDDA reaction is driven by the electrophilicity of the tetrazine, coupled with the high exothermicity of the reaction with the strained alkene . Faster kinetics can be achieved by increasing the strain of the TCO by adding cis ‐cyclopropane or increasing the electron deficiency of the tetrazine . However, the biological potential of this reaction is limited by size, aqueous stability and ease of synthesis of both the tetrazine and TCO, thus underscoring the importance of accessibility and practicality as equally important considerations to that of speed (Scheme ).…”
Section: Methodsmentioning
confidence: 99%